Comportamento tribológico do ABS aditivado com éster de pentaeritritol em ensaio de desgaste por deslizamento - Faria, Adiniele Martins de (2022)
The search for optimization and improvement of properties of polymeric materials using additive elements is a continuous demand because they have much applicability in several industrial sectors. The objective of the present work is to study the tribological behavior of ABS (Acrylonitrile Butadiene Styrene) with the addition of pentaerythritol esters (R1 and R2) through sliding wear test. The materials were processed in a twin-screw extruder (processing temperature 95 – 230 °C and 334 rpm) and later injection molded (processing temperature 210 – 230 °C, injection pressure 850 – 650 bar and cooling time of 5 sec.) for make the samples. The study samples were ABS and ABS with additive contents of 5, 10 and 15 (wt %) of pentaerythritol ester resin (R1) and pentaerythritol ester resin modified with maleic anhydride (R2) Test of tensile, hardness, thermogravimetry (TGA), Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectroscopy (FTIR) was performed to evaluate the characteristics of each material. Tribological performance was evaluated through pin-on-disk test at room temperature, constant speed and three loading levels 23.7, 47.4 and 71.1 N. After tribological test, analyzes via Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray spectroscopy (EDX) were performed. The results shows that the incorporation of resins into the polymer matrix does not significantly modify the mechanical and chemical properties of ABS, however they can reduce degradation temperatures. In view of the tribological results, to reduce the coefficient of kinetic friction, the sample containing the resin R2 is preferred over the samples containing R1. On the other hand, the incorporation of R1 pentaerythritol ester resin to reduce the wear rate showed more promising results compared to the other resin. The predominant slip wear mechanisms identified for these materials were abrasion and adhesion.